2012
DOI: 10.1158/1055-9965.epi-11-0786
|View full text |Cite
|
Sign up to set email alerts
|

Serum Macrophage Inhibitory Cytokine-1 (MIC-1/GDF15): A Potential Screening Tool for the Prevention of Colon Cancer?

Abstract: Background: Macrophage inhibitory cytokine-1 (MIC-1/GDF15) mediates nonsteroidal anti-inflammatory drug (NSAID) protection from colonic polyps in mice and is linked to the development of colorectal carcinoma in humans. Therefore, changes in serum MIC-1/GDF15 levels could predict the presence of premalignant colonic polyposis and assist in population screening strategies.Methods: Serum MIC-1/GDF15 levels were measured in subjects in the Polyp Prevention Trial, in which NSAID use and colon cancer risk factors we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 35 publications
(41 reference statements)
4
51
0
Order By: Relevance
“…Human GDF-15 expression is controlled by p53, which is linked to atherosclerosis and cancer (Yang et al, 2003). It has been shown that GDF-15 level is elevated in several cancers, including prostate, ovarian, pancreatic, and colorectal cancers and multiple myeloma (Staff et al, 2010;Breit et al, 2011;Wallin et al, 2011;Brown et al, , 2009Brown et al, , 2012Corre et al, 2012). In some cancer types, elevated levels of GDF-15 have been associated with adverse prognosis (Brown et al, 2009;Staff et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Human GDF-15 expression is controlled by p53, which is linked to atherosclerosis and cancer (Yang et al, 2003). It has been shown that GDF-15 level is elevated in several cancers, including prostate, ovarian, pancreatic, and colorectal cancers and multiple myeloma (Staff et al, 2010;Breit et al, 2011;Wallin et al, 2011;Brown et al, , 2009Brown et al, , 2012Corre et al, 2012). In some cancer types, elevated levels of GDF-15 have been associated with adverse prognosis (Brown et al, 2009;Staff et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas reports thus far have investigated mainly regulation of MIC-1 at a transcriptional level, here we have uncovered a novel post-transcriptional mechanism by which MIC-1 expression can be regulated. Due to its high levels within certain cancers such as gastric, colorectal, prostate, ovarian, and breast cancer and its close association with the presence particularly of premalignant colonic diseases, MIC-1 is being explored as a marker of tumor progression and a prognostic serum biomarker (10,33,34). However, our understanding of the signaling pathways involving MIC-1 within the context of tumor development is still incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…However, this analysis was limited by the large variation in the time of MIC-1 measurement with respect to colonoscopy, which compromises its ability to determine whether MIC-1 elevation was a predisposing factor or consequence of colorectal adenoma. (40) For IL-6 and TNF-α, the only available study did not find any association with risk of recurrent adenomas. (38)…”
Section: Introductionmentioning
confidence: 98%